2011
DOI: 10.1097/gim.0b013e3182035931
|View full text |Cite
|
Sign up to set email alerts
|

von Willebrand disease

Abstract: von Willebrand disease (VWD) is a common inherited bleeding disorder characterized by excessive mucocutaneous bleeding. Characteristic bleeding symptoms include epistaxis, easy bruising, oral cavity bleeding, menorrhagia, bleeding after dental extraction, surgery and/or childbirth and in severe cases, bleeding into joints and soft tissues. There are three subtypes: types 1 and 3 represent quantitative variants and type 2 is a group of four qualitative variants: 1) type 2A - characterized by defective von Wille… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
99
1
3

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 92 publications
(105 citation statements)
references
References 104 publications
2
99
1
3
Order By: Relevance
“…Intracellular retention of VWF is already known as a common mechanism for type 1 VWD. 6 The occurrence of intron retention rather than exon 44 skipping implies that the given mutation does not have any impact on the accuracy of splicing at 39ss. Therefore, it can be safely concluded that although bioinformatics predictions suggest interference with cis-SREs (supplemental Table 4), this disease-causing silent mutation would not exert its pathological influence through this mechanism.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Intracellular retention of VWF is already known as a common mechanism for type 1 VWD. 6 The occurrence of intron retention rather than exon 44 skipping implies that the given mutation does not have any impact on the accuracy of splicing at 39ss. Therefore, it can be safely concluded that although bioinformatics predictions suggest interference with cis-SREs (supplemental Table 4), this disease-causing silent mutation would not exert its pathological influence through this mechanism.…”
Section: Discussionmentioning
confidence: 99%
“…5 Inheritance of type 1 VWD is considered to be autosomal dominant; however, in ;15% of index cases, more than a single candidate VWF variant is detected. [6][7][8] Pre-mRNA splicing is regulated by consensus core splicing sites comprising the 59 splice site (59ss), the 39 splice site (39ss), and the branch point sequences. 9 The splicing reaction is initiated by RNA-RNA base pairing of the consensus 59ss motif and the U1 small nuclear RNA (snRNA) terminus, which is followed by excision of the 59 end of the intron, ligation of the adjacent exons, and releasing of the intron.…”
Section: Introductionmentioning
confidence: 99%
“…For the purposes of this study, we also include patients with an abnormal tendency to thrombus formation in our definition. Currently, 90% of BPD cases that do not have hemophilia 5 or von Willebrand disease 6,7 (VWD) never receive a conclusive molecular diagnosis due to the unavailability of affordable genetic tests. 8 Hence treatment is compromised in some cases and the rapid identification of affected relatives may be impeded.…”
Section: Introductionmentioning
confidence: 99%
“…La degradación proteolítica de los multímeros es un evento normal, ya que estos tienen un elevado potencial trombogénico, por los sitios de interacción con las plaquetas, y la pared de los vasos sanguíneos. En condiciones de homeostasis esta reacción inhibe el crecimiento del trombo que forman las plaquetas 16,17 .…”
Section: Factor De Von Willebrandunclassified
“…Por lo tanto, las 3 funciones fisiológicas de la proteína son: A) Mediar la adhesión de las plaquetas a los sitios de daño vascular al unirse al receptor plaquetario GpIb/IX, y al colágeno en el subendotelio vascular. B) Facilitar la agregación plaquetaria por medio de su unión al receptor plaquetario GpIIb/IIIa; y C) Unirse al FVIII y protegerlo de la degradación proteolítica provocada por la proteína C activada en el torrente sanguíneo 16 . Finalmente, estos contactos alcanzan un umbral que señala el evento de la activación plaquetaria.…”
Section: Factor De Von Willebrandunclassified